Understanding the role of Keggin type heteropolyacid catalysts for glycerol acetylation using toluene as an entrainer - Kale, S. S.; Armbruster, U.; Eckelt, R.; Bentrup, U.; Umbarkar, Shubhangi B. (Applied Catalysis A-General, 2016)
The heterogeneously catalyzed esterification (acetylation) of glycerol toward triacetin in batch mode in presence of toluene as entrainer was studied. Silicotungstic acid, tungstophosphoric acid and phosphomolybdic acid as heteropolyacids (HPAs) supported on silica, alumina or silica-alumina were used as catalysts. The course of the reaction was found to be very sensitive to the nature of the HPA as well as the support. Solid characterization by Raman spectroscopy, XRD, and pyridine-FTIR revealed that only combinations of tungsten-based HPAs and silica support were able to preserve the structure of active component throughout the preparation process, which was essential to obtain active and selective catalysts. The interaction between HPA and support was decisive for stability and dispersion of the catalytically active species. With the best performing catalyst H4SiW12O40/SiO2, selectivity to triacetin reached 71% at complete conversion within 24h. The high selectivity to triacetin is attributed the Brensted acidic sites originated from stabilized Keggin structure and continuous removal of water during course of reaction. Toluene is able to form azeotropic mixtures with water and acetic acid and keeps the reaction temperature below the boiling point of acetic acid. Thus, water-free reaction conditions can be established. The catalyst was reusable; however, the activity and selectivity towards triacetin slightly decreased in a repetition run due to loss of active sites. (C) 2016 Elsevier B.V. All rights reserved.